Pengaruh Literasi Keuangan Syariah Terhadap Minat Menabung Pada Bank Tabungan Negara ( Btn Kc Syariah Medan ) - Novia Ramadan; Salman Nasution (CERED Indonesia Institute, 2022)
The purpose of this study was to determine the effect of Islamic financial literacy on interest in saving at Bank BTN KC Syariah Medan. This type of research uses quantitative research. The population in this study is the customers of Bank BTN KC Syariah Medan which is located on Jl. Haji Juanda No. 48, The field and samples used were 78 samples using the Arikunto theory. Data collection techniques used in this study are questionnaires and observations. The analytical model used in this study is a regression analysis model, with a partial test method with Ttest. The results of the T test partially show that Islamic financial literacy has a positive effect on interest in saving. So it can be concluded that there is an influence of Islamic financial literacy on interest in saving at Bank BTN KC Syariah Medan.